Pengaruh Model Discovery Learning Terhadap Hasil Belajar Peserta Didik Kelas X Materi Perubahan Lingkungan Di SMA St Arnoldus Janssen Kupang (JBIOEDRA: Jurnal Pendidikan Biologi, 2024)
Low student learning outcomes are caused by a learning process that is still dominated by teachers. As a result, students only receive and memorize the delivered information, with limited opportunities to actively and creatively engage in the process of discovering knowledge independently. Therefore, selecting an appropriate learning model that aligns with the concepts and materials taught significantly influences the learning process. The purpose of this study is to determine the effect of the discovery learning model on the learning outcomes of Grade X students in environmental change material at SMA St. Arnoldus Janssen Kupang. This research employs a quantitative approach with a quasi-experimental design. The specific research design used is the nonequivalent control group design. The research sample consisted of Grade XA students as the experimental class, applying the discovery learning model, and Grade XB students as the control class, using direct instruction. Data analysis techniques include descriptive and inferential analyses. The results show that the discovery learning model effectively improves student learning outcomes. This is evident from the pretest average score of 52.8, which increased to 89 in the posttest. Based on the ANCOVA test, the significance value was 0.001 < 0.05. From these findings, it can be concluded that the discovery learning model significantly impacts the learning outcomes of Grade X students in environmental change material at SMA St. Arnoldus Janssen Kupang.
Keywords: Environmental Change Material, Discovery Learning Model, Learning Outcomes.